Gyretes brullé (Coleoptera: Gyrinidae) from Brazil: Morphology of eggs and early instars - Colpani, Daniara; Benetti, Cesar João; Hamada, Neusa; Andrade-Souza, V.; Michat, Mariano Cruz (Zootaxa, 2018)
Taxonomic information regarding Gyrinidae is mostly based on adults, especially due to the difficulty in collecting immatures and assigning them to a particular species. Association between immatures and adults is sometimes difficult because closely related species can be found in the same habitat. To solve this problem a feasible technique is rearing under laboratory conditions. However, this method is challenging because larval survival rate is usually low, and emulation of natural conditions is difficult. Molecular techniques, especially the use of the COI gene, have been applied to identify species and to associate different life stages. However, in some species groups this marker has not been successful in distinguishing closely related species. The objectives of this study are to describe the egg and the first two instars of Gyretes nubilus Ochs, 1965 and the egg of G. minax Ochs, 1967 and to evaluate the utility of COI to associate immatures and adults. The association of these immature stages with adults was done either rearing adults under laboratory conditions or by using DNA sequence data (COI), corroborating the utility of this molecular marker to associate immature and adults in Gyretes. These immature stages are described, including chaetotaxic analysis of larvae for the first time for the genus Gyretes Brullé, 1835. The eggs are described based on scanning electron microscopy. The eggs are similar to those of other Gyrinidae genera in having a micropylar region in the anterior pole and a longitudinal fissure, and by the absence of an aeropyle, but they differ mainly in characters related to chorionic structure and reticulation. Larvae of Gyretes can be distinguished from those of the other Neotropical Gyrinidae genera by a combination of several characters, including the frontoclypeal seta FR3 short, presence of three conspicuous additional setae on lateral region of parietal (contiguous to stemmata), and posterior margin of lacinia smooth, with apex not indented. Copyright © 2018 Magnolia Press.
Keywords: Animals; Beetle; Ecosystem; Larva; Ovum; Animal; Coleoptera; Ecosystem; Larva; Ovum